Pengaruh Model Problem Based Learning (PBL) Terhadap Hasil Belajar Siswa Sekolah Dasar - Anis Khoirunnisa; Putri Zudhah Ferryka; Cintya Mayawati (Jurnal Kajian dan Penelitian Umum, 2023)
This study aims to investigate the effect of the Problem Based Learning (PBL) Model on learning outcomes of elementary school students. Program Based Learning is a learning method that focuses on problem solving, in which students will be given realistic and complex problems to solve independently or in groups. This method is different from conventional learning methods which focus more on explaining theory and teaching directly from the teacher. The research method used was quasi-experimental using a pretest-posttest control group design. The research sample consisted of two classes of elementary school students in a city in Indonesia, namely one class as the control group and one class as the experimental group that applied the PBL Model. Data collection was carried out by giving pre-test before treatment and post-test after treatment to the two sample groups. The data were then analyzed using the independent sample t-test statistical technique. The results showed that there was a significant difference between student learning outcomes in the experimental group using the PBL model and the control group using conventional learning methods. The results showed that there was a significant difference between the learning outcomes of students using the PBL method and conventional learning. The group of students who received learning with the PBL method had a higher posttest average score than the control group. Therefore, it can be concluded that the use of the PBL model can positively influence the learning outcomes of elementary school students and it is recommended to apply it in the learning process in elementary schools.